The Th17 pathway in the peripheral lung microenvironment interacts with expression of collagen V in the late state of experimental pulmonary fibrosis - Fabro, Alexandre T. [UNESP]; Silva, Pedro H. R. Q. da; Zocolaro, William S.; Almeida, Mozar S. de; Rangel, Maristela P.; Oliveira, Cristiano C. de [UNESP]; Minatel, Igor O. [UNESP]; Prando, Erika d. C. [UNESP]; Rainho, Claudia A. [UNESP]; Teodoro, Walcy R.; Velosa, Ana P. P.; Saber, Alexandre M. A.; et al. (Elsevier B.V., 2015)
Background: Myofibroblasts derived from fibroblasts in the pathogenesis of pulmonary fibrosis causes excessive and disordered deposition of matrix proteins, including collagen V, which can cause a Th17-mediated immune response and lead to apoptosis. However, whether the intrinsic ability of lung FBs to produce the matrix depends on their site-specific variations is not known.Aim: To investigate the link between Th17 and collagen V that maintains pulmonary remodeling in the peripheral lung microenvironment during the late stage of experimental pulmonary fibrosis.Methods: Young male mice including wild Balb/c mice (BALB, n = 10), wild C57 Black/6J mice (C57, n = 10) and IL-17 receptor A knockout mice (KO, n = 8), were sacrificed 21 days after treatment with bleomycin. Picrosirius red staining, immunohistochemistry for IL-17-related markers and "in situ" detection of apoptosis, immunofluorescence for collagen types I and V, primary cell cultures from tissue lung explants for RT-PCR and electron microscopy were used.Results: The peripheral deposition of extracellular matrix components by myofibroblasts during the late stage is maintained in C57 mice compared with that in Balb mice and is not changed in the absence of IL-17 receptor A; however, the absence of IL-17 receptor A induces overexpression of type V collagen, amplifies the peripheral expression of IL-17 and IL-17-related cytokines and reduces peripheral lung fibroblast apoptosis.Conclusion: A positive feedback loop between the expression patterns of collagen V and IL-17 may coordinate the maintenance of peripheral collagen I in the absence of IL-17 receptor A in fibrosis-susceptible strains in a site-specific manner. (C) 2014 Elsevier GmbH. All rights reserved.
Keywords: Bleomycin-induced pulmonary fibrosis; Collagen V; IL-17 pathway; IL-17R knockout mice; Myofibroblast